Ion Homeostasis and Metabolome Analysis of Arabidopsis 14-3-3 Quadruple Mutants to Salt Stress - Gao, Jing; van Kleeff, Paula J. M.; de Boer, Mark H.; Erban, Alexander; Kopka, Joachim; Hincha, Dirk K.; de Boer, Albertus H. (Frontiers in Plant Science, 2021)
Salinity is one of the major abiotic stresses that limit agricultural productivity worldwide. Many proteins with a defined function in salt stress adaptation are controlled through interaction with members of the 14-3-3 family. In the present study, we generated three 14-3-3 quadruple knock-out mutants (qKOs: klpc, klun and unpc) to study the role of six non-epsilon group 14-3-3 proteins for salt stress adaptation. The relative growth inhibition under 100 mM NaCl stress was the same for wild-type (Wt) and qKOs, but the accumulation of Na+ in the shoots of klpc was significantly lower than that in Wt. This difference correlated with higher expression of the HKT1 gene in klpc. Considering the regulatory role of 14-3-3 proteins in metabolism and the effect of salt stress on metabolite accumulation, we analyzed the effect of a 24 h salt treatment on the root metabolome of nutrient solution grown genotypes. The results indicate that the klpc mutant had metabolome responses that were different from those of Wt. Notably, the reducing sugars glucose and fructose were lower in klpc under control and salt stress and their phosphorylated forms, glucose-6P and fructose-6P, were lower under salt stress as compared to Wt. This study provides insight into functions of 14-3-3 proteins from the non-epsilon group members. In combination, these proteins control ion homeostasis and metabolite composition under salt stress conditions and non-stressed conditions. Analysis of single, double and triple mutants that modify subsets from the most effective qKO mutant (klpc) may reveal potential redundancy for the observed phenotypes.